Study and Implementation of Internet of Things (IoT) Based Forest Fire Automation System to Detect and Prevent Wildfire - Sarasvathi, Nahalingham; Chelsea, Ferdyanti Kosasih (INTI International University, 2018)
The study and development objective of this project is to mitigate the regional and global phenomenon known as wildfire or forest fire through the implication of Internet of Things technology. ‘Early fire detection is recognized as a key element in improving protection of forests from fires’ (Sheikh Mohammad Ferdoush, 2014). The working principle of forest fire automation incorporates blocks of the functional circuit and sensor modules that are assembled as a unit thus, functioning to monitor the circumstances of a particular forest. Environmental sensors such as temperature and gas sensors are deployed to analyze the heat level and detect smoke presence generated by fire respectively. The utilization of passive infrared motion detector also helps in preventing disturbance from wildlife to the sensors scattered in the forest hence cutting down unnecessary cost and achieve its purpose of the secured system. The proposed system enhances the effectiveness of forest fire prevention by providing a solution for early discovery and quick response to combat forest fire.